KEBIJAKAN AKUNTANSI DAN PENYUSUNAN LAPORAN KEUANGAN UMKM (PAGUYUBAN PELAKU USAHA BANYUMAS) - Siti Maghfiroh; Khrisnhoe Rachmi Fitrijati (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2023)
MSMEs are one of the pillars to improve the country's economy, including Banyumas Regency, which was initiated by the Banyumas Association of Business Actors. In order for MSMEs to develop properly, information is needed for managers in making decisions. One form of information that is useful in the decision-making process by the owner or manager is accounting information. MSME accounting is an information system that identifies, manages, and communicates MSME economic information. Economic information is useful for decision making. One of the points to improve MSMEs is the effectiveness of financial management which is reflected through accounting policies and financial reporting. Financial statements are a process of transactions, recording processes and ultimately become financial reports. The financial statements consist of: balance sheet, income statement and notes to financial statements. The service which takes place at the Association of Banyumas business actors is carried out to provide knowledge and skills in managing finances and compiling financial reports.